The Correlation of Subfatin and Vitamin D3 in Obese and Normal Weight PCOS Patients - Abdulwahid, Walaa N.; Obaid, Reem M. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Polycystic ovarian syndrome (PCOS) is a complex endocrine problem affecting women with an estimated global prevalence of 9%, due to inherited and environmental causes. PCOS mainly impacts women aged 15-35 years, and women who are at their earliest or final period of pregnancy. Subfatin is a newly identified hormone that controls metabolism and is thought to be a biomarker for PCOS and metabolic syndrome. Vitamin D3 has an important function in the development of PCOS.Objective: To explore the effect of obesity on Subfatin and D3 levels, and the impact of the pathophysiology of PCOS on Subfatin and D3 levels.Methods: The total number of participants was 120: 80 females with PCOS, divided to 40 obese and 40 normal-weight, and 40 healthy females (controls). The current investigation was carried out from July to December 2024 at Kamal Al-Samarrai hospital in Baghdad, Iraq. The enzyme-linked immunosorbent assay (ELISA) was used to determine the subfatin serum levels. Body mass index, follicle-stimulating hormone (FSH), testosterone, estrogen, D3, and luteinizing hormone (LH) levels were all assessed. The data were examined with the origin lab software version 25. The study groups were compared using Analysis of variance (ANOVA).Results: Serum levels of subfatin, waist circumference, LH, estrogen, and testosterone were significantly higher (P < 0.001) in PCOS women compared to the control group. FSH besides the D3 levels was lower in PCOS cases than in healthy females.Conclusion: High levels of subfatin and low vitamin D3 levels might be implicated in the fundamental mechanisms of PCOS, irrespective of body weight.